Analisis Implementasi Pengendalian Internal Atas Kas, Persediaan dan Pembelian di UMKM Gudange Tahu Takwa Kediri - Nadia Rachma Dwiyanti; Rida Perwita Sari (Ekonomis: Journal of Economics and Business, 2023)
SMEs has a huge contribution on the Gross Domestic Product (GDP). But apparently SMEs still faced lots of challenges. One of which is managerial problem that can be overcome by digitalization. The implementation of accounting system is one of the conditions for the formation of large and strong business. On the implementation of accounting system, the existance of internal control system is needed to ensure the system is running efficiently. This research aims to analyze how the SMEs implement the internal control system. The research method is qualitative research using interview, observation and documentation as the data collection methods. The research shows that UMKM Gudange Tahu Takwa has implement the internal control system well, though there are still employee who has dual roles, and the practice of the physical cash count and stock opname are not in accordance with the existing theory.